2020
DOI: 10.1093/cid/ciaa1612
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Syncytial Virus Disease Severity in Young Children

Abstract: Background Respiratory syncytial virus (RSV) is the leading cause of acute respiratory infections (ARI) in hospitalized children. Although prematurity and underlying medical conditions are known risk factors, most of these children are healthy, and factors including RSV load and subgroups may contribute to RSV-ARI severity. Therefore, we aimed to evaluate the role of RSV in ARI disease severity and determine factors associated with increased RSV-ARI severity in young children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 26 publications
4
31
0
Order By: Relevance
“…Compared with non-GII.4, the clinical feature of GII.4-associated AGE is more severe, especially in diarrhoea and abdominal pain (Desai et al, 2012 ; Leshem et al, 2013 ). Our data indicated that “GII.4” group had a longer diarrhoea duration and a greater maximum number of diarrhoeal stools per day than those with “Others” group (both p < 0.05), which was consistent with previous studies (Haddadin et al, 2020 ; Wang et al 2019a ). The MVS has been used in several studies of norovirus infections to evaluate the severity of AGE (Bhavanam et al, 2020 ; Wang et al 2016a ).…”
Section: Discussionsupporting
confidence: 92%
“…Compared with non-GII.4, the clinical feature of GII.4-associated AGE is more severe, especially in diarrhoea and abdominal pain (Desai et al, 2012 ; Leshem et al, 2013 ). Our data indicated that “GII.4” group had a longer diarrhoea duration and a greater maximum number of diarrhoeal stools per day than those with “Others” group (both p < 0.05), which was consistent with previous studies (Haddadin et al, 2020 ; Wang et al 2019a ). The MVS has been used in several studies of norovirus infections to evaluate the severity of AGE (Bhavanam et al, 2020 ; Wang et al 2016a ).…”
Section: Discussionsupporting
confidence: 92%
“…It might be expected, if confounding by limitations of enrollment to only the most ill children was influential, that the proportions of enrolled children with RSV and influenza detection might have increased, not decreased, especially since RSV and influenza are important causes of severe ARI in children. [16][17][18][28][29][30][31] Both RSV and influenza activity show natural fluctuations from season to season such that the decrease in RSV and influenza detections in our study might be partially explained by seasonal variation or even differences in virulence of circulating viral strains. 14,15,17 The use of four seasons of data from the same study sites using similar enrollment criteria across wide geographic settings makes secular seasonal and virulence trends less likely to explain our findings of abrupt curtailment of RSV and influenza circulation among children in the study sites.…”
Section: Discussionmentioning
confidence: 67%
“…RSV is a major cause of ARI hospitalizations in young children during the fall and winter months and associated with significant morbidity. 16,17 We found a greater than 70% decrease in RSV-positive ARI in the community mitigation period in 2020 compared to the same period in prior surveillance seasons during which similar enrollment protocols were used. Baker et.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“… 1 , 18 , 19 Given that the vast majority of prior surveillance studies are cross-sectional, they potentially underestimate the full illness spectrum of RSV-associated healthcare utilization across clinical settings in the United States. 1 , 6 , 18 , 20 22 For example, in a population-based surveillance study among children under 5 years, 61% of RSV-positive children were hospitalized and 39% were seen in ambulatory care (i.e. EDs, pediatric offices).…”
Section: Discussionmentioning
confidence: 99%